Genomic and ecological approaches to identify the Bifidobacterium breve prototype of the healthy human gut microbiota - Argentini, Chiara; Lugli, Gabriele Andrea; Tarracchini, Chiara; Fontana, Federico; Mancabelli, Leonardo; Viappiani, Alice; Anzalone, Rosaria; Angelini, Leonora; Alessandri, Giulia; Longhi, Giulia; Bianchi, Massimiliano G.; Taurino, Giuseppe; et al. (Frontiers in Microbiology, 2024)
Members of the genus Bifidobacterium are among the first microorganisms colonizing the human gut. Among these species, strains of Bifidobacterium breve are known to be commonly transmitted from mother to her newborn, while this species has also been linked with activities supporting human well-being. In the current study, an in silico approach, guided by ecology-and phylogenome-based analyses, was employed to identify a representative strain of B. breve to be exploited as a novel healthpromoting candidate. The selected strain, i.e., B. breve PRL2012, was found to well represent the genetic content and functional genomic features of the B. breve taxon. We evaluated the ability of PRL2012 to survive in the gastrointestinal tract and to interact with other human gut commensal microbes. When co-cultivated with various human gut commensals, B. breve PRL2012 revealed an enhancement of its metabolic activity coupled with the activation of cellular defense mechanisms to apparently improve its survivability in a simulated ecosystem resembling the human microbiome.